2022
DOI: 10.1542/peds.2022-060071
|View full text |Cite
|
Sign up to set email alerts
|

Firearm-Related Injuries and Deaths in Children and Youth

Abstract: Firearms are the leading cause of death in children and youth 0 to 24 years of age in the United States. In 2020, firearms resulted in 10,197 deaths (fatality rate 9.91/100,000 youth 0-24 years old). Firearms are the leading mechanism of death in pediatric suicides and homicides. Increased access to firearms is associated with increased rates of firearm deaths. Substantial disparities in firearm injuries and deaths exist by age, gender, race, ethnicity, and sexual orientation and gender identity and for deaths… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 161 publications
2
27
0
Order By: Relevance
“…We noted that powder firearms were responsible for the majority of the fractures in the ≤5 and 11–16-year-old groups (78.7% and 67.1%) but only 44.1% for the non-powder firearm group ( Figure 3 e) and that the majority (63.3%) of those in the ≤5-year-old group occurred at home ( Figure 6 ). This confirms and supports the need for firearms in the home to be safely stored and locked and away from children [ 44 , 45 , 46 ]. It has been estimated that even in 2020 that 4.6 million US children live in homes with at least one loaded and unlocked firearm [ 47 ].…”
Section: Discussionsupporting
confidence: 74%
“…We noted that powder firearms were responsible for the majority of the fractures in the ≤5 and 11–16-year-old groups (78.7% and 67.1%) but only 44.1% for the non-powder firearm group ( Figure 3 e) and that the majority (63.3%) of those in the ≤5-year-old group occurred at home ( Figure 6 ). This confirms and supports the need for firearms in the home to be safely stored and locked and away from children [ 44 , 45 , 46 ]. It has been estimated that even in 2020 that 4.6 million US children live in homes with at least one loaded and unlocked firearm [ 47 ].…”
Section: Discussionsupporting
confidence: 74%
“…Our findings Unintentional injuries to young children are unspeakably tragic, but strategies have been developed to address the upward trend we observed. 1 Our results depict that unintentional injuries were disproportionately burdensome to younger adolescents. In addition to legislative forms of primary prevention, studies have shown secondary prevention strategies, such as anticipatory guidance with parents, safe-storage counseling, and provisions of firearm safes or lockboxes, to be effective in reducing FRI in youth and young adults.…”
mentioning
confidence: 73%
“…In December 2022, the American Academy of Pediatrics published a policy statement on firearm-related injuries and deaths in children and youth and offered strategies for injury prevention and harm reduction (Lee et al, 2022b). Pediatric nurses have many interactions with children, youth, and their families.…”
mentioning
confidence: 99%